THE EFFECTS OF SERVICE QUALITY ON CUSTOMER'S SATISFACTION IN FITNESS CENTER IN SEMARANG, INDONESIA - -, Suyatman; Lertwachara, Kaveepong (Journal of Business And Entrepreneurship, 2022)
This study was designed to explore the level of service quality and its effects on customer satisfaction. Data were collected from 420 men and women from 14 fitness centers. The findings showed that four dimensions such as assurance, empathy, reliability, responsiveness, of perceived service quality had a higher value than expected service quality. Tangible dimension was the only dimension that did not meet customer expectations. Based on the regression analyses, responsiveness was the only variable that had negative effect on S1 (specific services provided). Basically, there was a positive relationship between service quality and overall satisfaction. Tangible dimension, empathy dimension, personal class, and membership had a positive relationship to overall satisfaction. Based on the findings, the managers of fitness center should consider responsiveness dimension because it has negative effect on specific services provided. Moreover, the researchers recommended that fitness centers should emphasize to increase the variables that have a positive effect on overall satisfaction.